Validity of the Polar V800 to measure vertical jump performance in taekwondo athletes - Pereira dos Santos, M. A.; Torres Cabido, C. E.; Oliveira Silvino, V.; Rodrigues de Mesquita, A.; Santos do Nascimento, F. L.; de Albuquerque Neto, S. L.; Naves de Oliveira Goulart, K.; Szmuchrowski, L. A.; Couto Pena, B. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2021)
Background. Lower limbs performance plays a huge role in the training processes of martial arts, including taekwondo. By mon itoring vertical jumps (VJ) lower limb muscular strength can be assessed. However, the force plate, considered the gold standard device to evaluate VJ performance, is expensive and lab-based. The Polar V800 device is able to measure VJ height, and it has become widely popular among trainers and athletes. However, it has not yet been validated for this purpose. Problem and aim. Due to the impracticability of using the force plate, coaches and athletes have been using the Polar V800 in their training routines. This study aimed to evaluate the validity and reliability of the Polar V800 versus force plate measurements to estimate VJ height in taekwondo athletes. Methods. Thirty male national level taekwondo athletes were asked to perform five squat jumps and five countermovement jumps at maximal effort on the force plate while simultaneously wearing the stride sensor connected to the V800. The mean and the highest jump measurements estimated simultaneously by both devices were compared through Pearson`s correlation and Bland-Altman test. Results. Intraday reliability of the V800 was excellent with ICCs ranging from 0.97 to 0.98. There was strong reliability (ICC > 0.97), a low standard error of measurements (0.69 - 0.92 cm), an excellent correlation between methods (r > 0.96), and excellent agreement observed by Bland-Altman analysis. Conclusion. The Polar V800 device is demonstrated to be a valid and reliable tool for the estimation of VJ height.